Trial Watch: Adoptive cell transfer for anticancer immunotherapy - Aranda, Fernando (Landes Bioscience, 2014)
The expression “adoptive cell transfer” (ACT) is commonly employed to indicate an immunotherapeutic regimen involving the isolation of autologous blood-borne or tumor-infiltrating lymphocytes, their selection/expansion/activation ex vivo, and their reinfusion into the patient, most often in the context of lymphodepleting pre-conditioning and in combination with immunostimulatory treatments. Optionally, the cellular material for ACT is genetically manipulated before expansion to (1) target specific tumor-associated antigens; (2) endogenously express immunostimulatory molecules; and/or (3) persist for long periods upon reinfusion. Consistent efforts have been dedicated at the amelioration of this immunotherapeutic regimen throughout the past decade, resulting in the establishment of ever more efficient and safer ACT protocols. Accordingly, the number of clinical trials testing ACT in oncological indications does not cease to increase. In this Trial Watch, we summarize recent developments in this exciting area of research, covering both high-impact studies that have been published during the last 12 months and clinical trials that have been launched in the same period to evaluate the safety and therapeutic potential of ACT in cancer patients.